Self-contained dual-scale composite architectures in spray dried zirconium diboride. Issue 12 (15th June 2022) - Makurunje, Phylis; Woodhouse, Guy; Goddard, David T.; Middleburgh, Simon C.
Abstract: Zirconium diboride microspheres are candidate nuclear fuel additives. Dual-scale composite architectures (DCA) were produced in spray dried and sintered zirconium diboride microspheres. These findings expand the conventionally accepted hollow ("shell"), partially hollow ("dimpled") and shrivelled ("wrinkled") architectures previously reported in literature. Three-dimensional architectures of internally and externally detailed features on the microscale have been characterised by scanning electron microscopy. Core-shell architectures reported have maximum Feret diameters between 216.4 ± 58.7 μm and 450.7 ± 79.9 μm, while clustered granulate architectures have maximum Feret diameters of 830.0 ± 86.4 μm. Calculated dimensionless Peclet, Weber and Ohnesorge numbers of 0.16–0.21, 28.3, and 0.6–1.3 were obtained, respectively, and related to the morphologies of the microspheres obtained. Not only does this study show that the resultant architecture can be obtained, but also that the spray dried granulate morphologies are dependent on the binder quantity used. Microsphere architectures have potential utility in the accommodation of fission products expected during reactor operation. Graphical abstract: Image 1